Occupational Exposure to 50 ppm Isoflurane Impairs Sperm Parameters in Mice - Zanin, Marina; Varela Junior, Antonio Sergio; Bonel Acosta, Izani; Anastacio Da Silva, Edenara; Bicca Dode, Maria Eduarda; Gehrcke, Martielo Ivan; Gobbo Braz, Mariana [UNESP]; Dahl Corcini, Carine (Wolters Kluwer, 2024)
Objectives The aims of the study are to assess the effect of occupational exposure to isoflurane on the sperm quality of mice and to investigate whether cessation of exposure can restore seminal quality. Methods Mice were exposed to 50 ppm of isoflurane for 5 hours per day over a 30-day period. Following this exposure, they were euthanized at predetermined postexposure intervals, and their sperm samples were analyzed for kinetics and viability parameters. Results Occupational exposure to isoflurane can adversely affect sperm at 50 ppm, a concentration deemed safe by international occupational health conventions in some countries. These effects are marked by oxidative stress, mitochondrial dysfunction, and genomic damage, alongside alterations in sperm kinetics and acrosomal integrity. Furthermore, cessation of exposure does not guarantee restoration of cellular quality. Conclusions Isoflurane at 50 ppm, previously deemed safe by some countries, impairs sperm kinetics and viability, potentially directing the spermatogenic process toward infertility and apoptosis.
Keywords: flow cytometer; infertility; isoflurane; occupational exposure; semen quality; sperm motility; waste anesthetic gas